(untitled) (Revista Cocar, 2014)
O Programa Institucional de Bolsas de Iniciação à Docência (PIBID) foi institucionalizado na Universidade do Estado do Pará em junho de 2011, após a aprovação do projeto institucional "Universidade e escola: desafios e caminhos para a form(ação) de professores no contexto amazônico". O objetivo consistiu em desenvolver ações que aproximassem alunos das licenciaturas em Pedagogia, Matemática, Ciências Naturais-Física, Geografia, Música e Educação Física dos processos e práticas cotidianas em escolas públicas assim valorizando a docência, enriquecendo a formação inicial e promovendo oportunidades para compreensão e avanço do ensino na região amazônica. Neste artigo, apresentamos um esboço geral da dimensão organizacional do PIBID-UEPA e, à luz do campo teórico da formação de professores, tecemos algumas considerações sobre as realizações e desafios do primeiro ano do programa, fundamentados na observação, análise de documentos e questionários de caracterização. Palavras-chave: PIBID." Formação de professores. The institutional program of teaching initiation scholarships (PIBID) at State University of Pará (UEPA): initial reflections The Institutional Program of Teaching Initiation Scholarships (PIBID-CAPES) was institutionalized in the in June 2011, after the institutional project entitled "University and school: challenges and paths to form teachers in the Amazonian context" was approved. The central goal was to develop actions that throughout 24 months would bring students from the licensing majors in Pedagogy, Mathematics, Natural Sciences-Physics, Geography, Music and Physical Education closer to daily processes and practices in public schools, praising scholarship, enriching initial formation and providing opportunities to comprehend the advance of teaching practices in the Amazon region. In this paper, we present data on the organizational dimension of the PIBID-UEPA to understand its institutional structure and, in light of the teacher formation theoretical field, we draw some considerations on the accomplishments and challenges of the programâ€™s first year, methodologically grounded in experience, systemized observation, in data from inventories and in interviews conducted with several program participants. Keywords: PIBID; teacher formation. " " " "